Live Load Deflections in a Prestressed Steel Beam Bridge - Welden, Neil (Engineering Journal, 1965)
The subject of this investigation is a 240 ft by 30 ft three span continuous prestressed steel beam bridge, skewed 30 degrees clockwise, over Silver Creek on U. S. Highway No. 6 in Pottawattamie County, Iowa. The spans are 73 ft, 3 in.—93 ft, 6 in.—73 ft, 3 in. The slab is supported by four lines of beams, spaced 9 ft, 8 in. center to center, spliced 22 ft, 0 in. each side of each interior support, near the point of dead load contra-flexure. The exterior beams are 30 WF 108, and the interior beams are 33 WF 130. All beams are ASTM A36 steel, and all have high strength steel cover plates. The design live load is AASHO H20-S16-44. Live load moments causing tension in the bottom flange and compression in the top flange of the beams are resisted by composite action of the beam and slab. The structure will hereafter be referred to as the Silver Creek Bridge.